Natural antioxidant from hibiscus sabdariffa extract: Assessments on extraction yield, antioxidant capacity and total polyphenol content of different polarities of solvent extracts / Nur Royhaila Mohamad ... [et.al.]. - Mohamad, Nur Royhaila; Abdul Gani, Siti Salwa; Abdul Wahab, Roswanira; Darham, Widyani (Universiti Teknologi MARA Cawangan Sarawak, 2022)
Hibiscus sabdariffa L. (H. sabdariffa, roselle; Malvaceae) has traditionally been used as food, in herbal drinks, hot and cold beverages, as a flavoring agent in the food industry and as herbal medicine. The effect of solvents (hexane, ethyl acetate and ethanol) on extraction yield, antioxidant capacity and polyphenol content were studied. The antioxidant capacities of the H. sabdariffa extracts were evaluated using a ferric reducing antioxidant power (FRAP) assay and the free-radical scavenging capacity was evaluated using 2,2-diphenyl-1-picrylhydrazyl (DPPH) assays. The polyphenols from H. sabdariffa extracts were determined by total phenolic content (TPC) and total flavonoid content (TFC). The ethanol extract showed the highest extraction yield (38.39  0.29%) and total antioxidant activity: DPPH (73.96  0.7%) and FRAP (72.93  2.4 mmol Fe2+ g−1). The same extract also exhibited the highest phenolic content (312.25  0.17 mg gallic acid equivalent g−1).